Understanding Consumer Purchase Intention through Augmented Reality Beauty Preview Perceived Effectiveness: The Moderating Effect of Online Customer Responses on E-Commerce Beauty Prod - Heddry Purba; Ria Chaniago (Economics and Digital Business Review, 2026)
The rapid growth of e-commerce and digital technology has transformed consumer decision-making processes, particularly in the beauty product industry where consumers face uncertainty in evaluating product suitability before purchase. This study aims to examine the influence of Augmented Reality Beauty Preview Perceived Effectiveness on consumer purchase intention and analyze the role of online customer responses in shaping purchasing decisions for beauty products on e-commerce platforms. This research adopts a quantitative approach using a survey method involving 114 Shopee users who have experience purchasing beauty products and interacting with Augmented Reality Beauty Preview features and online customer responses. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The results indicate that Perceived Effectiveness has a positive and significant effect on purchase intention, demonstrating that consumers are more likely to purchase when they perceive Augmented Reality Beauty Preview technology as useful, efficient, and effective in supporting product evaluation. Furthermore, online customer responses have a positive and significant influence on purchase intention, indicating that consumer-generated information strengthens trust and reduces uncertainty in online purchasing decisions. The findings also show that the integration of technology-based experiences and social information provides a better understanding of consumer behaviour in digital marketplaces. This study contributes to the digital consumer behaviour literature by extending the UTAUT perspective through the integration of Augmented Reality Beauty Preview Perceived Effectiveness and online customer responses in explaining purchase intention within the beauty e-commerce context